A shift in the ligand responsiveness of thyroid hormone receptor alpha induced by heterodimerization with retinoid X receptor alpha. - Claret, F X (1996)
Thyroid hormone (T3) receptors (T3Rs) are ligand-modulated transcription factors that bind to thyroid hormone response elements (T3REs) and mediate either positive or negative transcriptional regulation of target genes. In addition, in response to ligand binding, T3Rs can interfere with AP-1 activity and thereby inhibit transcription of AP-1-responsive genes. T3Rs were recently shown to form heterodimers with retinoid X receptors (RXRs), leading to increased binding to T3REs in vitro and potentiation of transcriptional responses in vivo. Here we demonstrate that T3R alpha forms stable heterodimers with RXR alpha in living cells. Most important, we describe a new role for RXR alpha in modulating ligand-dependent T3R alpha activity: heterodimerization with RXR alpha greatly increases transcriptional interference with AP-1 activity, augments T3-dependent transcriptional activation, and potentiates the reversal of ligand-independent activation by T3R alpha. In all three cases, the responses occur at substantially lower T3 concentrations when elicited by T3R alpha plus RXR alpha than by T3R alpha alone. In vitro, the binding of T3 decreases the DNA-binding activity of T3R alpha homodimers but does not affect DNA binding by T3R alpha:RXR alpha heterodimers. We provide evidence that increased activities of T3R alpha at lower T3 concentrations are not due to changes in its T3 binding properties. Instead, the altered response could be mediated by either RXR alpha-induced conformational changes, increased stability of heterodimers over homodimers, especially following T3 binding, or both.